Constitutional status of the President of the Republic of Armenia - Bożyk, Stanisław (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The article is devoted to the political position and role of the president of the Republic of Armenia. In it, the author analyses the transformations of the constitutional status of this supreme state body, together with subsequent amendments to the constitution, which have been made several times since the collapse of the USSR and Armenia’s acquisition of full sovereignty in 1991. The Constitution of 1995 shaped the position of the president in reference to the semi-presidential model, granting him a superior role in relation to other organs of the state, including the parliament. However, his powers were significantly limited after the 2005 amendment to the constitution. The status of the Armenian president has changed even more after the last revision of the constitution in 2015, which finally departed from the semi-presidential model and introduced a parliamentary system of government. Under this system, the president of Armenia has been assigned the role of head of state and the constitution does not even include it expressis verbis among the organs of the executive power.